2017
DOI: 10.1111/spc3.12307
|View full text |Cite
|
Sign up to set email alerts
|

Hegemonic masculinity versus a caring masculinity: Implications for understanding primary caregiving fathers

Abstract: Recently, there has been a growing interest in what is positioned as a new form of masculinity arising from the increase in fathers as primary caregivers. This new form is referred to as a “caring masculinity” and is theorised as a radical shift away from traditional or hegemonic forms of masculinity. This paper critically examines the fathering literature, focusing specifically on how primary caregiving fathers navigate social norms with regard to masculinity. The paper concludes that there is a complex inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 63 publications
2
98
1
5
Order By: Relevance
“…We interpret this framing as one that connects with the maintenance of a more traditional if not hegemonic masculinity. While earlier research suggests that caring and hegemonic masculinities 'sit alongside one another' (Hunter et al, 2017) and that caring masculinity is somehow incorporated into hegemonic masculinity (Hearn et al, 2012), we have shown that this is neither uncomplicated nor clear in the lives of men. New masculinities offer young male academics not only opportunities to embrace care responsibilities, but their lives are rendered notably complex.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…We interpret this framing as one that connects with the maintenance of a more traditional if not hegemonic masculinity. While earlier research suggests that caring and hegemonic masculinities 'sit alongside one another' (Hunter et al, 2017) and that caring masculinity is somehow incorporated into hegemonic masculinity (Hearn et al, 2012), we have shown that this is neither uncomplicated nor clear in the lives of men. New masculinities offer young male academics not only opportunities to embrace care responsibilities, but their lives are rendered notably complex.…”
Section: Discussioncontrasting
confidence: 97%
“…Caring masculinities offer an alternative model based on caregiving roles for men (Scambor et al, ). While care is traditionally associated with femininity (Scambor et al, , p. 560), men in many societies in the Global North are now expected to be more involved in caregiving (Hunter et al, ). In anglophone research, caring masculinities are presented as new forms of masculinity arising from, for example, increase in fathers as primary caregivers (Hunter et al, ).…”
Section: Hegemonic Vs Caring Masculinitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hess Brown & DeRycke, ). This appears to remain the case, despite increased expectations around the adoption of caring masculinities for fathers and their involvement in family life and childcare (Hunter, Riggs, & Augoustinos, ).…”
Section: Mothering In a Digital Agementioning
confidence: 99%
“…Similarly, both the time availability and the relative resources perspectives (Aassve et al, 2014;Craig & Mullan, 2011;Hook & Wolfe, 2011a), as well as aspects of Sen's capabilities theory (Hobson, 2013), can be drawn upon to explain how fathers' family and household context impact participation in childcare. Finally, gender role theory and the concept of caring masculinities (Banchefsky & Park, 2016;Elliott, 2016;Hunter, Riggs, & Augoustinos, 2017;Kangas, Lämsä, & Heikkinen, 2017) provide useful mechanisms that help explain the ways values and belief systems underpin the decisions fathers make regarding caregiving within the work and family/household contexts. For each theory I first describe its original application, and then describe how it has been applied to explaining differences between fathers' patterns of participation.…”
Section: Explanations For Differences In Paternal Participation In Chmentioning
confidence: 99%